ARTISTIC ANALYSIS OF PHILOSOPHICAL PLOTS IN LITERATURE - Eshmatova Yulduz Boymakhmatovna (Modern American Journals, 2025)
This scientific article provides detailed information about the interpretation and manifestation of the female image in folklore literature and genre. Therefore, in the article, opinions are expressed about the image and interpretation of women in folklore, and the methods of its illumination. In addition, the history of folklore, the stages of its formation, and the interpretation of characters are highlighted.